Widening inequality: The evolution of the motherhood penalty in China (1989–2015). (October 2022) - Shen, Chao
The motherhood penalty is an important issue in the field of family and gender inequality research. China has experienced rapid economic growth and drastic social change in recent decades, but existing studies fail to provide an overview of changes in the effect of the motherhood penalty during this period. This article uses data from the China Health and Nutrition Survey from 1989 to 2015 and applies a multi-layer mixed-effects model to study the severity of the motherhood penalty and the various mechanisms affecting it over that period. This study shows the following: (a) childbirth has a negative impact on women's wages and the severity of this impact continues to increase, showing that the effect of the motherhood penalty has become harsher over time; (b) although the motherhood penalty was initially lower for single mothers than for married ones, it has increased for both groups of women over the period and the rate of growth has been much faster for single mothers and, thus, the difference between the two groups in terms of the effect of the motherhood penalty has narrowed gradually over the period; (c) the long-term effect of the motherhood penalty is normally less pronounced than the short-term effect, but the long-term effect has grown at a much quicker rate over recent years compared with the short-term effect, and in more recent years these two effects are almost the same; (d) the higher the education level of women, the lower the effect of the motherhood penalty, but as the effect of the penalty has intensified over the period of study, the difference across different education levels has decreased; and (e) the effect of the motherhood penalty on female employees in the non-state sector is greater than that on female employees in the state sector, and the effect of the motherhood penalty on female employees in the non-state sector has increased rapidly, while the change has remained slow in the state sector, resulting in a widening gap between the two sectors. This study shows that the dramatic social and economic change in recent decades has subjected women to greater and greater maternal responsibilities but has afforded them disproportionately fewer benefits in relation to economic development.